Burst Spinal Cord Stimulation: A Clinical Review. (1st June 2019) - Kirketeig, Terje; Schultheis, Carsten; Zuidema, Xander; Hunter, Corey W; Deer, Timothy
Abstract: Objective: Clinical review on outcomes using burst spinal cord stimulation (SCS) in the treatment of chronic, intractable pain. Design: Narrative clinical literature review conducted utilizing a priori search terms including key words for burst spinal cord stimulation. Synthesis and reporting of data from publications including an overview of comparative SCS outcomes. Results: Burst SCS demonstrated greater pain relief over tonic stimulation in multiple studies, which included blinded, sham-controlled, randomized trials. Additionally, burst stimulation impacts multiple dimensions of pain, including somatic pain as well as emotional and psychological elements. Patient preference is weighted toward burst over tonic due to increased pain relief, a lack of paresthesias, and impression of change in condition. Conclusion: Burst SCS has been shown to be both statistically and clinically superior to tonic stimulation and may provide additional benefits through different mechanisms of action. Further high-quality controlled studies are warranted to not only elucidate the basic mechanisms of burst SCS but also address how this unique stimulation signature/pattern may more adequately handle the multiple affective dimensions of pain in varying patient populations.